Genome-wide association study of asthma exacerbations despite inhaled corticosteroid use. Issue 5 (13th May 2021) - Hernandez-Pacheco, Natalia; Vijverberg, Susanne J.; Herrera-Luis, Esther; Li, Jiang; Sio, Yang Yie; Granell, Raquel; Corrales, Almudena; Maroteau, Cyrielle; Lethem, Ryan; Perez-Garcia, Javier; Farzan, Niloufar; Repnik, Katja; et al.
Rationale: Substantial variability in response to asthma treatment with inhaled corticosteroids (ICS) has been described among individuals and populations, suggesting the contribution of genetic factors. Nonetheless, only a few genes have been identified to date. We aimed to identify genetic variants associated with asthma exacerbations despite ICS use in European children and young adults and to validate the findings in non-Europeans. Moreover, we explored whether a gene-set enrichment analysis could suggest potential novel asthma therapies. Methods: A genome-wide association study (GWAS) of asthma exacerbations was tested in 2681 children of European descent treated with ICS from eight studies. Suggestive association signals were followed up for replication in 538 European asthma patients. Further evaluation was performed in 1773 non-Europeans. Variants revealed by published GWAS were assessed for replication. Additionally, gene-set enrichment analysis focused on drugs was performed. Results: 10 independent variants were associated with asthma exacerbations despite ICS treatment in the discovery phase (p≤5×10 −6 ). Of those, one variant at the CACNA2D3-WNT5A locus was nominally replicated in Europeans (rs67026078; p=0.010), but this was not validated in non-European populations. Five other genes associated with ICS response in previous studies were replicated. Additionally, an enrichment of associations in genes regulated by trichostatin A treatment was found. Conclusions: The intergenic region of CACNA2D3 and WNT5A was revealed as a novel locus for asthma exacerbations despite ICS treatment in European populations. Genes associated were related to trichostatin A, suggesting that this drug could regulate the molecular mechanisms involved in treatment response. A genome-wide association study of asthma exacerbations despite inhaled corticosteroid treatment in childhood asthma revealed a novel association at the CACNA2D3 - WNT5A locus and suggested trichostatin A as a potential asthma therapy https://bit.ly/3nxWLPD